Stable Mixed‐Valent Radicals from Platinum(II) Complexes of a Bis(dioxolene) Ligand. Issue 21 (2nd February 2014) - Loughrey, Jonathan J.; Sproules, Stephen; McInnes, Eric J. L.; Hardie, Michaele J.; Halcrow, Malcolm A.
Abstract: Three diplatinum(II) complexes [{PtL}2 (μ‐thea)] (H4 thea=2, 3, 6, 7‐tetrahydroxy‐9, 10‐dimethyl‐9, 10‐dihydro‐9, 10‐ethanoanthracene) have been prepared, with diphosphine or bipyridyl "L" co‐ligands. One‐electron oxidation of these complexes gave radical cations containing a mixed‐valent [thea     . ] 3− ligand with discrete catecholate and semiquinonate centers separated by quaternary methylene spacers. The electronic character of these radicals is near the Robin–Day class II/III border determined by UV/Vis/NIR and EPR spectroscopies. Crystal‐structure determinations and a DFT calculation imply that oxidation of the thea 4− ligand may lead to an increased through‐space interaction between the dioxolene π systems. Abstract : Electron hopping : Diplatinum complexes, such as the one shown here, are readily oxidized to mixed‐valent catechol/semiquinone radical species, some of which can be crystallized at room temperature. The dioxolene rings in the radical products are moderately strongly coupled by EPR and UV/Vis/NIR spectroscopies, despite being separated by saturated methylene spacers.